Ankle sprain injuries in soccer players aged 7-15 years during a one-year season - Kofotolis, N. (Biology of Exercise, 2014)
Although ankle sprains are common in soccer, the role of various risk factors in soccer players aged 7-15 is unclear. The purpose of this study was to examine whether incidence of ankle sprain injuries, associated time loss of participation, and injury risk factors are associated with chronological age in soccer players aged 7-15 years. A sample of 677 male soccer players was divided in three age groups: between 7 and 9 years (U9), between 9 and 12 years (U12) and between 12 and 15 years (U15). Ankle sprain injury incidence, participation time loss, injury mechanisms, ankle region injured, and other risk factors were recorded in games and practice sessions using questionnaires for one year. During the study 38 ankle injuries were recorded, of which 27 were ankle sprains. These led to 182.7 sessions lost (on average, 6.71 lost sessions per injury). There was an increased risk of ankle injury in U15 group compared with U12 (relative risk = 2.34; 95% confidence interval, 1.28 to 5.02) while no injuries for the U9 were observed. Most incidents (66.7%) were contact injuries with the highest injury risk displayed by goalkeepers. Injury rate was higher in games than in practice and increased in the second half of the match (P < .05). Multinomial logistic regression showed that history of previous injury was a significant predictor of ankle sprain in the U15 group (relative risk = 1.69; 95% confidence interval, 1.0 to 2.9). Age is an important factor for soccer training because many clubs use chronological age to separate their young players into teams. This study showed that children less than 9 years showed no injury risk while players older than 12 years showed a higher risk. Injury rate was, however, lower than that reported previously for adult players. Injury prevention strategies may be particularly useful for young adolescent soccer players.